Viajantes em busca de saídas : o grupo de movimento como uma possível rota terapêutica para usuários de álcool e de outras drogas - Rasch, Scheila Silva (2005)
It considers the applicability of movement groups as a therapeutic strategy for alcohol and drug users. The policy of the Brazilian Ministry of Health on the use of alcohol and other drugs encourages differentiated strategies of intervention for such users, aiming their sheltering, considering not only abstinence, but also practices of harm reduction as reference. It takes as context of its study the Center of Prevention and Treatment of Toxic Maniacs, Secretary of Health, City of Vitória the first Center of Psychosocial Attention Alcohol and Drugs in the State of Espírito Santo and its main lines of work. It traces the history of the movement group from 1995 to 2003, having as study subjects the participants of the movement group sessions that took place from November 2002 to May 2003. It uses documentary research, having as source the management reports of the mentioned institution, patients reports, documents and planning reports of the movement group sessions. It works with semi-structured interviews in order to search for the interpretation given by the participant subjects in the process. It brings the interpretation of the interviewed subjects on such experience, highlighting the repetition of effects produced by the work, such as sensations of vitalization and relaxation which may establish new practices capable of helping patients to reposition their history and their utilization patterns of psychoactive substances. It points out the viability of movement groups as a possible therapeutic resource for such users, safeguarding the uniqueness of this clientele through actions such as the offer of open groups, considering the difficulty of these users for joining a group as well as continuing their treatment.